Relationship between Aerobic Endurance and Movement Coordination with Single Kick Skills - Ihsan, Nurul; Syafrizal, Syafrizal (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Background and aim. Single kick skill is one of the fundamental techniques in pencak silat that requires optimal physical condition and motor ability. Aerobic endurance supports athletes in maintaining performance during matches, while movement coordination plays a crucial role in executing accurate and effective kicking techniques. This study aimed to determine the relationship between aerobic endurance and movement coordination with single kick skills in young Indonesian martial arts (SMI) athletes in Pariaman City.Methods. This research employed a correlational design. The population consisted of 20 SMI athletes (17 males and 3 females) in Pariaman City. The sample was determined using purposive sampling, involving 17 male athletes. Aerobic endurance was measured using the bleep test, movement coordination was assessed using the soccer wall volley test, and single kick skills were evaluated through a performance test assessed by judges. Data were analyzed using Pearson product moment correlation with a significance level of α = 0.05.Results. The findings revealed: (1) a significant relationship between aerobic endurance and single kick skills (t_count = 2.29 > t_table = 1.75); (2) a significant relationship between movement coordination and single kick skills (t_count = 2.48 > t_table = 1.75); and (3) a significant simultaneous relationship between aerobic endurance and movement coordination with single kick skills (F_count = 8.23 > F_table = 3.74).Conclusions. Aerobic endurance and movement coordination are significantly related to single kick skills, both partially and simultaneously. Improving these physical and motor components may contribute to better single kick performance in pencak silat athletes.